Identifying the essential components of cultural competence in a Chinese nursing context: A qualitative study - Duanying Cai (2018)
© 2016 John Wiley & Sons Australia, Ltd. This qualitative study using semi-structured interviews was conducted to identify the essential components of cultural competence from the perspective of Chinese nurses. A purposive sample of 20 nurse experts, including senior clinical nurses, nurse administrators, and educators in transcultural nursing, was recruited. Using thematic analysis, four themes: awareness, attitudes, knowledge, and skills, with two subthemes for each, were identified. Notably, culture in China was understood in a broad way. The participants’ responses focused upon demographic attributes, individuality, and efforts to facilitate quality care rather than on the cultural differences of ethnicity and race and developing the capacity to change discrimination or health disparities. A greater understanding of cultural competence in the Chinese nursing context, in which a dominant cultural group exists, is essential to facilitate the provision of culturally competent care to diverse populations.